(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
In the context of sectoral digitalization and the necessity to respond to contemporary challenges, the implementation of situationally adapted hybrid learning in the field of general education has become increasingly significant. During the pandemic, the application of hybrid education through a situational approach enabled the relatively uninterrupted continuation of the educational process. However, it should be noted that social pedagogues were not adequately prepared to carry out their professional functions, especially when different models of hybrid learning were implemented in response to specific situational features. Working across two environments—online and physical—requires social pedagogues to possess new professional competencies that align with the characteristics and demands of both traditional and hybrid learning formats. In this context, the functions of the social pedagogue are being redefined and supplemented, based on the principles and methodology of hybrid learning. The professional activity of the social pedagogue is undergoing a process of reinterpretation in accordance with the requirements of situational learning.